Knowledge alumism between literature and grammar in the Arab heritage - ALSHMAKHI, AISHA KASSIM MOHMMAD (Al-Adab Journal, 2022)
Many Arabic language sciences have a relationship with each other and organic correlation, and although some topics and interests vary from science to science, this has not prevented the apparent correlation and overlap between them.The importance of this study is that it examines between two important polar sciences in Arabic sciences, old and new, as a model on the twashj.This study aims to explore the depths of the relationship between literature and grammar in the Arab heritage, and to clarify its manifestations, old and new, and this study came to answer several questions, including: What are the manifestations of cognitive correlation between Arabic literature and Arabic grammar?, what is the role of literature in the genesis and development of grammar?, is the cognitive correlation between literature and grammar increasing or decreasing?This study followed the descriptive inductive approach, as they prioritized the study of manifestations of cognitive ization among scientists.The study summarized a set of findings: that grammar and its rules are necessary to understand meaning and analyze literary texts and that towards the text of modern studies that confirm the manifestations of this combination of literature and grammar.